2013
DOI: 10.1002/14651858.cd006715.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia for cardiac surgery

Abstract: This meta-analysis of studies, identified to 2010, showed that the use of TEA in patients undergoing coronary artery bypass graft surgery may reduce the risk of postoperative supraventricular arrhythmias and respiratory complications. There were no effects of TEA with GA on the risk of mortality, myocardial infarction or neurological complications compared with GA alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Thoracic epidural analgesia (TEA) leads to a significantly decreased risk of AKI development post CABG surgery [32] . However, Svircevic et al [33] produced conflicting results suggesting the risk of TEA usage in a patient who may require full heparinisation. Nonetheless, the use of epidural analgesia in cardiac surgery has been associated with a reduction in mortality [34] .…”
Section: Epidural Anaesthesiamentioning
confidence: 99%
“…Thoracic epidural analgesia (TEA) leads to a significantly decreased risk of AKI development post CABG surgery [32] . However, Svircevic et al [33] produced conflicting results suggesting the risk of TEA usage in a patient who may require full heparinisation. Nonetheless, the use of epidural analgesia in cardiac surgery has been associated with a reduction in mortality [34] .…”
Section: Epidural Anaesthesiamentioning
confidence: 99%
“…A larger cohort study examining the use of TEA in patients undergoing cardiac surgery found a decreased need for dialysis (160). The results of these studies must be balanced by the failure of a Cochrane Database Review to show a mortality reduction in patients undergoing cardiac surgery who received TEA (161) as well as the potential risk associated with the use of TEA in a patient who may require full heparinization.…”
Section: Prevention Of Aki Nonpharmacologic Strategiesmentioning
confidence: 99%
“…Moreover, epidural analgesia has been associated with a reduction in patient mortality, but the beneficial effect was rather low (number needed to treat (NNT) = 70). Other authors did not observe a higher risk of epidural hematoma in cardiac surgery patients than in general surgery patients [23,24]. The risk of hematoma after PVB in cardiothoracic surgery seems to be even lower [25,26].…”
Section: Discussionmentioning
confidence: 86%